FATORES CONDICIONANTES DE SUCESSO E SOBREVIVÊNCIA DE MICRO E PEQUENAS EMPRESAS NO MUNICÍPIO DE VALENÇA - RIO DE JANEIRO - Matos, Everton Guimarães (2009)
A r e s e a r c h c on du c t e d b y S ys t em SEBRAE in 2 00 4 shows th a t c e r t a i n c o nd i t i on s , pr o c e s s e s a nd man a geme n t s t yl e s l e a ds to a pr ema tu r e c l os i n g o f th ou s and s o f sma l l bu s i n e s s . Some o f t h e ma in c a u s e s o f t hi s e a r l y b u s i n e s s i nt e r r u pt i on a r e th e l a c k o f kn owl ed ge a s we l l a s th e l a c k o f c e r t a i n co nd i t i on s a nd f a c t or s s u ch a s su pp or t a v a i l a bi l i t y, b a s i c i n fo rma t io n, t e chn i c a l sk i l l s , ma rk e t in g, a dmi ni s t r a t i v e r ou t in e s , n e go t i a t i on s sk i l l s , a c c e s s t o c r e di t l i n e s , pr e p a r a t i on of f i n an c i a l p r op os a l s , hi s to r y i n th e ma rk e t , f in a nc i a l an a l ys e s a n d pr e p a r a t i on of a b us in e s s p l an . Some of th e me nt i on e d c au s e s a r e v e r y c o n s i s t e nt in ma n y c a s e s , c r e a t in g a n imp o r t ant imp a c t on th e e co nomy o f t h e St a t e o f Ri o d e J an e i r o. Fo r th a t r e a s on a p ro po s a l f o r a c t ion s a nd pr oj e c t s t h a t c ou ld h e lp t o minimi z e th e n umbe r o f c omp a ni e s t ha t a r e c l os i n g t h e i r do o r s d u e to l a c k of s up po r t i s v i t a l . Th e p ro p os a l o f th i s d i s s e r t a t i on i s to ge t f ami l i a r i z ed wi t h th e ma i n s t r e n gt hs an d we a k ne s s e s of t h e e n t r e p r en eu r s , i n th e e a r l y s t a ge s o f t h e i r ini t i a t i v e s o f o p eni n g a b us ine s s , wi th t he i nt ent io n o f p ro po s i n g th e u s e o f to ol s t h a t c o uld max imi z e th e ne e d ed sk i l l s o f th e fut u r e in d ep e nd e nt b us in e s sma n. For th a t pu r po s e a me tho d olo g y wi t h a p r agma t i c co nt e nt wi l l ma k e u s e of sur v e ys t hr ou gh qu e s t io nn a i r e s an d in t e r v i ews , u s i n g a s ampl e of nin e new e nt r ep r en e u r s o f Va l en ç a -RJ , r i s in g f r om th e SEBRAE-RJ . Th e c o l l e c t ed in f orma t io n co uld b e u s ed f or th e d e v e l opme nt o f t r a i ni n g an d c ons ul t ing p r o gr am, ma in l y f o c us e d on th e a dmin i s t r a t iv e a nd f i n an c i a l a r e a .So , t h e di s s e r t a t i on ha s th e o bj e c t i v e o f s howi n g th a t , thr o u gh t h e us e o f t r a i nin g a n d c o nsu l t in g p r o gr ams i t i s p os s i bl e t o imp ro v e ma n a geme nt ski l l s o f t h e fu tu r e bu s i n e s smen a nd a l so r e du c e th e n umb e r o f e a r l y d e a th s o f sma l l b us in e s s .